PREDICTION MODEL FOR TIDAL FLOOD CONTROL USING ONE-WAY COUPLING SCHEME IN PONTIANAK, WEST KALIMANTAN - Randy Ardianto; Aris Ismanto; Sugeng Widada; Joko Sampurno (JURNAL TEKNIK HIDRAULIK, 2022)
Tidal flood prediction is an important part of action plans in disaster mitigation. The lack of information about the time, duration and location of potential events in the pre-disaster stage, can lead to greater damage and losses. This study aims to fill the pre-disaster information gap by designing a short-term prediction system for tidal flood in the Pontianak City using one-way coupling model scheme. The scheme collaborates weather prediction model (WRF-ARF), hydrodynamic model (DELFT3D), and hydraulic model (HEC-RAS). The validation of the flood prediction map using the contingency table method by 67 survey points, indicates a good accuracy with a Hanssen-Kuipper Skill score = 0.77 – 0.91. Furthermore, based on the simulation, it was found that the potential for flood areas in Pontianak is around 15.10% - 16,03% of the city area. Hence, this area should be the focus for the local government to take preventive action to reduce the potential disasters in the future. Generally, this study has succeeded in integrating models in various dynamic aspects to predict tidal flood and the model framework can be recommended in tidal flood early warning systems.Keywords: Prediction; Tidal Flood; WRF-ARW; DELFT3D; HEC-RAS 2D; Pontianak